Observation on the curative effect of long intestinal tube in the treatment of phytobezoar intestinal obstruction. Issue 11 (March 2019) - Li, Liang; Xue, Bing; Zhao, Qiang; Xie, Hong-Qiang; Luan, Xue-Rong; Cui, Qing
Abstract : Abstract: The aim of the study was to observe the curative effect of long intestinal tube (LT) in the treatment of phytobezoar intestinal obstruction. We performed a retrospective study of patients with phytobezoar intestinal obstruction who underwent decompression with different tube insertion method. A total of 80 patients were collected and divided into nasogastric tube (NGT) group (n = 36) and LT group (n = 44) between August 2015 and August 2018 at our hospital. Univariate analysis was used to assess the clinical efficacy of 2 groups of patients. There were no significant differences in the mean age, sex ratio, and previous surgical history between the 2 groups. There were statistically significant differences between the 2 groups in terms of improvement time of clinical indications (4.2 ± 1.4 vs 2.5 ± 0.6 days; P  = .008), liquid decompression amount on the first day of catheterization (870.4 ± 400.8 vs 1738.4 ± 460.2 mL; P  = .000), transit operation rate (4/36 vs 0/44; P  = .023), clinical cure rate (25/36 vs 40/44; P  = .014), total treatment efficiency (32/36 vs 44/44; P  = .023), and total hospitalization cost (3.25 ± 0.39 vs 2.07 ± 0.41 ¥ ten thousand; P  = .000). The curative effect of LT in the treatment of phytobezoar intestinal obstruction is accurate and reliable, which can effectively improve the clinical symptoms of patients, comprehensively improve the non-surgical rate of intestinal obstruction treatment, reduce the total cost of hospitalization, and is worthy of promotion in clinical application.